Women's political empowerment and social protection responses to COVID-19. Issue 3 (3rd July 2022) - Huang, Fang-Yi; Lin, Jiun-Da
ABSTRACT: The association between women's political empowerment and social spending in welfare regimes is well established, but research on the association with social protection responses to COVID-19 is just beginning. This paper looks at the association between women's political empowerment index (WPEI) and the scopes of social protections found in individual countries. Poisson regression models were used with datasets from the Goble Database on Social Protection and Jobs Responses to COVID-19, World Development Indicators, and V-Dem to identify national and regional differences in social protection coverage. The findings indicate the countries with higher WPEI values have greater ranges of social protections. In particular, there is a significantly positive association between degree of women's political empowerment in the form of civil society participation and social protection scope. Our results provide new evidence suggesting that increasing women's civil society participation is a clear pathway to improving social protection scope.